Adaptasi Sel terhadap Perubahan Lingkungan Osmotik - Paulus Rudirudolof Ekaputra; Sumira Sumira; Yohana Fransiska Doi; Emanuel Ohaq; Veronika P. Sinta Mbia Wae (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to examine the mechanism of cell adaptation to hypertonic conditions through osmoregulation processes in various types of cells and organisms. The method used is a systematic literature review of 30 national and international journal articles sourced from Google Scholar and ScienceDirect databases. Articles were selected based on inclusion criteria that include topic suitability, availability of osmotic experimental data, and relevance to cellular responses. The results of the study indicate that cells adapt through the accumulation of compatible osmolytes such as proline, glycine betaine, and sorbitol to maintain intracellular water and ion balance. This response was observed in various objects, including Rhoeo discolor cells that showed optimal adaptation to 0.26 M sucrose with a decrease in plasmolysis from 85% to 36%, and Inpari rice seeds with an increase in drought tolerance of up to 50% through proline accumulation. Active osmoregulation was also found in frog erythrocytes, Lactobacillus plantarum, tiger prawns (543-610 mOsm/L), and tilapia which recorded an 80% survival rate at graded salinities. In general, increased osmoregulatory capacity significantly reduced cell damage from hypertonic stress, although the magnitude of the response varied among organisms. These findings have important implications for the development of rainfed agriculture, brackish water aquaculture management, and the selection of genotypes resistant to extreme climate change.